(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To compare the changes in the number of acne lesions before and after treatment with auricular acupuncture targeting the Endocrine, Subcortex, Lung, Heart, and Stomach points combined with 0.1% adapalene, and to assess the adverse effects of this combination treatment after 4 weeks. Method: A single-group interventional study was conducted to evaluate the effectiveness of auricular acupuncture combined with 0.1% adapalene before and after treatment in 33 acne patients, and to assess adverse effects after 4 weeks of treatment. Results: After 4 weeks of treatment combining auricular acupuncture at the Endocrine, Subcortex, Lung, Heart, and Stomach points with 0.1% adapalene, the number of inflammatory acne lesions significantly decreased from 2 (0-6) to 0 (0-2) (p<0.05) compared to before treatment. No adverse effects were reported from the combined treatment during the 4 weeks. Conclusion: This pilot study has shown that combining auricular acupuncture with adapalene may offer potential for safe and effective treatment of acne vulgaris, warranting further in-depth research.